To find the equation of the line that passes through the points provided in the table, we will first calculate the slope (m) of the line using the formula:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} \]
Let's use the points (3, 6) and (6, 4):
- \( (x_1, y_1) = (3, 6) \)
- \( (x_2, y_2) = (6, 4) \)
Now we can calculate the slope:
\[ m = \frac{4 - 6}{6 - 3} = \frac{-2}{3} \]
Now that we have the slope, we can use point-slope form of the line equation, which is:
\[ y - y_1 = m(x - x_1) \]
Using the point (3, 6):
\[ y - 6 = -\frac{2}{3}(x - 3) \]
To convert this into standard form \(Ax + By = C\), we will start with the point-slope form obtained:
\[ y - 6 = -\frac{2}{3}(x - 3) \]
First, multiply each term by 3 to eliminate the fraction:
\[ 3(y - 6) = -2(x - 3) \]
Expanding both sides gives:
\[ 3y - 18 = -2x + 6 \]
Now, rearranging to standard form \(Ax + By = C\):
\[ 2x + 3y = 24 \]
Thus, the standard form of the equation of the line going through the points in the table is:
\[ 2x + 3y = 24 \]
Now, looking at your provided options, the correct choice is:
2x + 3y = 24.